Effect of the change in antiviral therapy indication on identifying significant liver injury among chronic hepatitis B virus infections in the grey zone - Ren, Shan; Wang, Wenjing; Lu, Junfeng; Wang, Kefei; Ma, Lina; Zheng, Yanhong; Zheng, Sujun; Chen, Xinyue (Frontiers in Immunology, 2022)
Objective In clinical practice, a substantial proportion of chronic hepatitis B virus (HBV) infections that do not fit into any of the usual immune states are considered to be in the “grey zone (GZ)”. This study aimed to investigate the effect of the change in antiviral therapy indication on identifying significant hepatic injury among GZ patients. Methods Patients with chronic HBV infections and a persistent normal alanine aminotransferase (ALT) level (PNALT) who underwent ultrasonography-guided percutaneous liver biopsy were examined retrospectively. Evidenced hepatic injury (EHI) was defined as an inflammation grade ≥2 (≥G2) and/or fibrosis stage ≥2 (≥F2). Complete clinical data, liver inflammation, and fibrosis grades were collected, and the levels of cytokines were detected by the Luminex technique, all of which were analysed to investigate the immune and histopathology states of the liver. Results A total of 347 patients with chronic HBV infections and PNALT were categorized into immune tolerant (IT, n = 108), inactive HBV surface antigen (HBsAg) carrier (IHC, n = 61), GZ-1 (HBeAg positive in GZ, n = 92), and GZ-2 (HBeAg negative in GZ, n = 68) phases. Among them, 51.3% were in the GZ phase, and 50.1% presented with EHI. The IL-6 levels were higher in the EHI group than in the non-EHI group (2.77 vs. 1.53 pg/ml, Z = −13.32, p = 0.028). The monocyte chemoattractant protein 1 (MCP-1) level was positively correlated with HBV DNA (R = 0.64, p < 0.001) and HBeAg (R = 0.5, p < 0.001) but negatively correlated with fibrosis grade (R = −0.26, p = 0.048). The ratio of EHI in the GZ phase was 60.55%, which was significantly higher than that in patients in the IT (39.8%) and IHC phases (37.7%) (χ2 = 10.4, p = 0.006). A total of 46.69% of all patients exceeded the new ALT antiviral treatment threshold (30 U/L for men and 19 U/L for women). The EHI values in the IT and IHC phases below the new ALT threshold were 32.6% and 37.8%, respectively, whereas higher EHI values of 67.4% and 68.4% were seen in GZ-1 and GZ-2 patients, respectively, exceeding the new ALT threshold, and the difference was statistically significant (χ2 = 11.13, p < 0.001; χ2 = 14.22, p = 0.002). The median age in our cohort was 38.91 years, and only 21.03% were less than 30 years old. The EHI values in the IT and IHC patients <30 years old were 32.4% and 35.8%, respectively, while the ratio of EHI increased to 43.2% once patients were older than 30 years but still in the IT and IHC stages. Conclusion Setting 30 years old as a cut-off and lowering the ALT threshold could facilitate screening for the presence of significant liver injury, especially for GZ patients. IL-6 was a good indicator of EHI, and MCP-1 was significantly positively correlated with HBV DNA but negatively correlated with liver fibrosis.